Early Childhood Education and Multicultural Awareness: A Case Study from Bangkalan, Madura - Ramdhan, Tri Wahyudi; Sholeh , Makherus (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2025)
Early childhood education plays a vital role in shaping children’s understanding of diversity and reducing biases. In an increasingly multicultural society, fostering multicultural awareness from an early age is essential for promoting inclusivity and empathy. This study explores how curriculum elements and classroom interactions influence young children’s awareness of diversity and bias reduction. Using a qualitative approach, data were collected through classroom observations, curriculum document analysis, and interviews with early childhood educators. The research examines the use of multicultural storybooks, diverse toys, and inclusive activities, as well as the role of teacher-child and peer interactions in encouraging positive attitudes toward cultural differences. The findings indicate that exposure to diverse cultural materials and teacher-led discussions significantly enhance children’s appreciation of diversity. Additionally, classrooms that actively promote inclusivity see reduced stereotyping and bias. The study provides practical insights for educators and policymakers, offering strategies to integrate multicultural content into curricula and foster inclusive, bias-free learning environments. These insights are valuable for those seeking to create more equitable early childhood education settings.